The Inter-Ethnic Student Social Interactions: The Case Study of a Public Senior High School in Batam - Martin, Yona; Efi, Agusti (Indonesian Research Journal in Education |IRJE|, 2023)
Various ethnic students have triggered social interaction forms, like looking for friends during break time to go to the cafeteria or sitting relaxed in the school park. Likewise, students tend to choose the optional extracurricular activities based on their friends because they are reluctant to get involved in an activity if their fellow friends are not in the group. This research aimed to identify forms of social interaction of students of different ethnicities at a public senior high school in Batam. It used qualitative with a case study approach. The participants were the student assistant principal, the English teacher, and students at a public senior high school in Batam. Data analysis used the interactive analysis model. The research results showed the associative social interaction forms were seen during extracurricular activities, collaboration in study groups, and classroom cleaning competitions. Meanwhile, the dissociative social interaction was used when the use of local languages during conflicts and disputes over student council elections.Â  Â